Can philosophy inoculate technoscience? Philosophy in licenciate distance learning courses - Diogo Bogéa (Arizona State University, 2018)
This article presents an investigation into the place of philosophy in licentiate distance learning courses. The Heideggerian reflections on "technology" and the "technological epoch" as essentially characterized by "pure calculation", which obliterates the possibility of an authentic philosophical experience, are well known. This article draws attention to another dimension of the relation between Philosophy and "technology" unexplored by Heidegger: the possibility that through the endless technological apparatus we have in our world, the passion for an authentic philosophical experience may reach people and places until very recently unreachable.